Sustainable Pharmaceutical Waste Management: Pharmacists and Patients Perception in Ghanaian Hospitals - Debrah, Justice Kofi (2022)
Pharmaceutical waste (PW) is known to be a health problem in developing countries, being harmful to human beings, animals, and the environment, with a high potential for the transmissibility of diseases. This study aims to address the implementation of strategies in the hospital context in Ghana, Africa, regarding the proper pharmaceutical waste management and the relationship with the environment and public health from both pharmacists and patients. Based on a questionnaire and observation, a cross-sectional exploratory-descriptive study with quantitative and qualitative approaches (mixed method) was carried out in selected hospitals in Ghana. A total of 111 responses were received, with 23 (76.7% rate response) being the professional pharmacists and 88 (60.7% rate response) from patients. The survey used random sampling, and the data collected were analyzed using SPSS version 27. The result shows that most of the participants were aware of what constitutes PW and had social awareness of PW. The majority of both types of respondents do not segregate PW, resulting in poor disposal. Unsegregated PW from the professionals was due to a lack of logistics like color-coding. The problems associated with PW in Ghana will be better managed through continued education and awareness at all levels to promote waste segregation